2010
DOI: 10.1074/jbc.m110.145219
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of E2–25K/UBB+1 Interaction Leading to Proteasome Inhibition and Neurotoxicity

Abstract: E2-25K/Hip2 is an unusual ubiquitin-conjugating enzyme that interacts with the frameshift mutant of ubiquitin B (UBB ؉1 ) and has been identified as a crucial factor regulating amyloid-␤ neurotoxicity. To study the structural basis of the neurotoxicity mediated by the E2-25K-UBB ؉1 interaction, we determined the three-dimensional structures of UBB ؉1 , E2-25K and the ), and polyglutamine-expanded huntingtin (2). UBB ϩ1 was first identified as a frameshift mutant of the ubiquitin (Ub) B protein in the brains of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 50 publications
3
67
1
Order By: Relevance
“…In addition, the interaction between E2-25K/Hip-2 and UBB(z1) may be critical for the synthesis and accumulation of UBB(z1)-anchored polyubiquitin, which results in proteasomal inhibition and death of the neurons. 21 Single nucleotide polymorphisms in the UBQLN1 gene have been linked to late-onset AD. Its protein product, ubiquilin-1, functions as a molecular chaperone for APP and leads to Abeta accumulation.…”
Section: Amyloid-beta and Ubiquitination Mutant Ub And Ubiquilinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the interaction between E2-25K/Hip-2 and UBB(z1) may be critical for the synthesis and accumulation of UBB(z1)-anchored polyubiquitin, which results in proteasomal inhibition and death of the neurons. 21 Single nucleotide polymorphisms in the UBQLN1 gene have been linked to late-onset AD. Its protein product, ubiquilin-1, functions as a molecular chaperone for APP and leads to Abeta accumulation.…”
Section: Amyloid-beta and Ubiquitination Mutant Ub And Ubiquilinmentioning
confidence: 99%
“…6 E2-25K is an unusual member of the E2 conjugating enzyme family in that it is competent to catalyze Ub chain extension independent of E3 ligases. 21 It functions upstream of apoptosis signal-regulating kinase 1 (ASK1) and c-Jun N-terminal kinase (JNK) in Abeta42 toxicity. 6 It contains a UBA domain that is unique to human E2 conjugating enzymes.…”
Section: Ubiquitination Enzymesmentioning
confidence: 99%
“…A number of studies have shown that neurotoxicity of Aβs is critical to pathogenesis of AD. A current report found that Aβs are also regulated by UPS components, such as E2-25/Hip2 and TRIP22 (Ko et al 2010). HRD1 regulates levels of APP in the AD brains in an Ubdependent manners (Kaneko et al 2010).…”
Section: Parkinson's Diseasementioning
confidence: 96%
“…The sequence of the 3D structures of UBA domains of Saccharomyces cerevisiae Ubc1 (pdb entry 1TTE (Merkley and Shaw, 2004)) and human Ube2 K (pdb entry 3K9P (Ko et al, 2010)) were used as query in Blast-p to retrieve other UBA domains of E2 family 1, sharing different degree of sequence similarity with the queries. Moreover, other UBA domains belonging to proteins different from E2 enzymes were retrieved by a Blast-p search in PDB.…”
Section: Identification Of Family 3 E2s Characterized By C-terminal Amentioning
confidence: 99%